2003
DOI: 10.1097/00126334-200309010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Protease Inhibitor Resistance–Associated Mutations in Plasma HIV-1 Precedes That in Proviruses of Peripheral Blood Mononuclear Cells by More Than a Year

Abstract: HIV-1 genotype assay using plasma viruses has been widely applied for detection of resistant viruses in infected individuals, whereas there are only a few reports about proviral genotype in peripheral blood mononuclear cells (PBMCs). To determine which sample, plasma or PBMC, should be used for early detection of drug-resistant viruses during antiretroviral treatment, we analyzed 275 plasma-derived and 211 PBMC-derived HIV-1 protease sequences obtained from HIV-1-infected patients during protease inhibitor (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 22 publications
6
35
0
Order By: Relevance
“…Since all patients in this study initiated HAART very recently and about half of the 11 patients in whom drug resistance mutations were detected still had a viral load of less than 5,000 copies/ml at the time of sampling, they can be considered early treatment failures. Although the number of patients is limited, a correlation between low viral load and a reduced capacity for the detection of resistance mutations in DNA compared to that of resistance mutations in RNA was observed, further strengthening the hypothesis of a relationship between duration of treatment failure and the ability to detect drug resistance in DNA, as was suggested by Bi et al (6).…”
Section: Continued On Facing Pagesupporting
confidence: 64%
See 2 more Smart Citations
“…Since all patients in this study initiated HAART very recently and about half of the 11 patients in whom drug resistance mutations were detected still had a viral load of less than 5,000 copies/ml at the time of sampling, they can be considered early treatment failures. Although the number of patients is limited, a correlation between low viral load and a reduced capacity for the detection of resistance mutations in DNA compared to that of resistance mutations in RNA was observed, further strengthening the hypothesis of a relationship between duration of treatment failure and the ability to detect drug resistance in DNA, as was suggested by Bi et al (6).…”
Section: Continued On Facing Pagesupporting
confidence: 64%
“…Some studies reported more mutations in the plasma RNA (6,10,21,24), and others reported more mutations in the cellular DNA (14,34). Most of these discordances may be attributed to differences in the selection of the samples used for the evaluation.…”
Section: Continued On Facing Pagementioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that wild-type proviruses are maintained, despite the emergence of drug resistance mutations in plasma (1,17,34,37,42). In one study, emergence of the M184V mutation was compared in genomic viral RNA and viral DNA; however, there was no attempt to distinguish the emergence of the mutations in the different species of viral DNA (37).…”
mentioning
confidence: 99%
“…Since we wished to study all patients (regardless of treatment history), including those with PVL below detection limit, we chose to perform resistance testing by targeting HIV-1 DNA from the PBMC proviral compartment, instead of the most commonly used plasma HIV-1 RNA. Although studies have found that the detection of resistance mutations in the HIV-1 RNA plasma compartment may precede that in PBMC (Kaye et al 1995, Bi et al 2003, it has been shown that HIV DNA recovered from the proviral compartment can reliably be used in drug resistance genotyping (Devereux et al 2000, Sarmati et al 2003, Chew et al 2005, Parisi et al 2007, Vicenti et al 2007). In addition, proviral sequences can be useful to detect archived mutations that can compromise future therapeutic options, such as those selected by previously used regimens (Sarmati et al 2003, SG Parisi et al unpublished observations), and have been found to have greater sensitivity after treatment interruption in treatment experienced patients (Venturi et al 2002).…”
Section: Discussionmentioning
confidence: 99%